2009
DOI: 10.1039/b916261p
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of Pd(0) on surface functionalised Fe3O4 nanoparticles: magnetically recoverable and stable recyclable catalyst for hydrogenation and Suzuki–Miyaura reactions

Abstract: We describe here a methodology to immobilise/stabilise metallic Pd on surface-functionalised ferrite nanoparticles leading to a magnetically separable catalyst, which exhibits efficient catalytic activity in various hydrogenation and ligand-free Suzuki-Miyaura reactions. Importantly, the use of highly branched polyethylenimine to entrap Pd nanoparticles on the surface of Fe 3 O 4 results in structurally stable catalytic sites, which makes them recyclable without any loss in activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(66 citation statements)
references
References 61 publications
0
66
0
Order By: Relevance
“…The catalyst also exhibited high activity toward various aryl bromides (entries [9][10][11][12][13][14][15][16][17][18][19]. Excellent yields were obtained for aryl bromides bearing electron-withdrawing substituents (entries [10][11][12][13][14].…”
Section: Heck Reactions Catalyzed By Fe 3 O 4 @Puvs-pd In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst also exhibited high activity toward various aryl bromides (entries [9][10][11][12][13][14][15][16][17][18][19]. Excellent yields were obtained for aryl bromides bearing electron-withdrawing substituents (entries [10][11][12][13][14].…”
Section: Heck Reactions Catalyzed By Fe 3 O 4 @Puvs-pd In Watermentioning
confidence: 99%
“…[13][14][15] The polymermodified magnetic nanoparticle-supported palladium catalysts have been prepared to simplify the separation steps while maintaining high activity and selectivity of palladium. [16][17][18][19] So far, in most of the studies concerning the applications of Fe 3 O 4 nanoparticle-supported catalysts, organic solvents, or mixed solvents containing DMF and NMP, are used as the reaction media. Du and co-workers 18 prepared a nanosized catalyst (Fe 3 O 4 /SiO 2 /HPG-OPPh 2 -PNP) by modifying Fe 3 O 4 /SiO 2 nanoparticles with glycerol and chlorodiphenyl phosphine.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous protocols for the reduction of aromatic nitro compounds have been reported in the literature [2][3][4][5][6][7]. They include: 1) hydrogenation under H 2 at various pressures promoted by various catalysts [8], such as Pt/C [9], Rh 3 Ni 1 [10], Pd/C [11][12][13], Pd [14,15] and Rh [16] nanoparticles; 2) catalytic reduction in the presence of CO and H 2 O [17] and photocatalytic hydrogenation [18]; 3) catalytic transfer hydrogenation promoted, for example, by Cu [19], Pd [20], palladium/graphene [21], Au [22], Ru [23] or Fe 3 O 4 -Ni [24] nanoparticles with reducing agents other than molecular hydrogen [25,26], including hydrazine [27][28][29][30][31][32], silanes [33,34] and sodium borohydride [35][36][37][38][39][40][41]. In this last case, large use of Au based catalysts has been explored [42].…”
Section: Introductionmentioning
confidence: 99%
“…14-18 Their unique physical properties make possible the complete recovery of the catalysts by means of an external magnetic field, which is an important advantage of the use of a magnetically separable catalyst. Rana et al 19 reported a funtionalised Pd/Fe 3 O 4 catalyst with highly branched polyethylenimine for hydrogenation and Suzuki-Miyaura reactions. The catalyst was proved to be quite efficient for a host of substrates in hydrogenation and Suzuki-Miyaura reactions.…”
Section: Introductionmentioning
confidence: 99%